Effect of Channa striata Extract Supplementation on Febrile Neutropenia in Acute Myeloid Leukemia Patients Undergoing Chemotherapy: A Randomized Controlled Study - Setiawan, Budi; Pangarsa, Eko Adhi; Santosa, Damai; Rizky, Daniel; Tandarto, Kevin; Suharti, Catharina (Asian Pacific journal of cancer prevention : APJCP, 2024)
Febrile neutropenia is one of the most serious complications in patients with hematological malignancies and chemotherapy. Channa striata is a freshwater fish belonging to the family Channidae. This study aims to determine whether the administration of channa striata extract can increase neutrophil count, neutrophil function and prevent incidence of febrile neutropenia in acute myeloid leukemia (AML) patients receiving chemotherapy. A randomized, single-blind, controlled study compared a standard nutrition from hospital with a channa striata extract-supplemented per oral containing 6 grams of channa striata extract in patients with acute myeloid leukemia undergoing intensive chemotherapy. To analyze the effects of channa striata extract on function of neutrophil, Interleukin (IL)-6 and nitric oxide (NO) levels which are the result of neutrophil phagocytosis were assessed. A total of 32 AML patients were randomized to receive per oral supplementation of channa striata extract (6 g/day) or nutrition from the hospital during intensive chemotherapy and after chemotherapy. The median onset of neutropenia was 6.1 + 3.37 in the channa striata extract group and 8.8 + 4.59 in the control group (p=0.109). The median duration of neutropenia was 12.8 + 6.20 d in the channa striata group and 17.2 + 11.06 d in the control group (p=0.281), whereas the incidence of febrile neutropenia were 85,7% in the channa striata extract group and 43,8% in the control group with median duration of neutropenic fever were 5.7 + 3.56 and 4.7 + 4.57, respectively. The chi-square test in the IL-6 delta category showed a tendency for IL-6 levels to rise in 61.5% of subjects in the Channa striata group compared to the control group (p=0.182). Channa striata extract supplementation did not influence neutropenia onset, duration, neutrophil function, or neutropenic fever in AML patients.